The Impact of Service Innovation as a Mediator Effecting on Intentions of Online Shopping Among LGBTQ + Consumers in Thailand. - Pantawan , Khunakon; Hinthaw, Kanjana (KKBS Journal of Business Administration and Accountancy, 2022)
Therefore, the objective of this research is to study the relationship between brand personality, social capital, service innovation and intention to purchase. Focusing on LGBTQ+ consumers who are currently facing higher consumption rates: 1) Do brand personality factors, social capital, and service innovation were positively correlated and influenced their intention to purchase online? 2) Is service innovation a mediating variable which has a mediating effect to the higher increase of intention to purchase online or not? A questionnaire was used as a tool and data were collected from 385 samples. Data were analyzed by descriptive statistics, reference statistics, and compositional analysis to assess the suitability of latent variables. The results of the study revealed that 1) brand personality, social capital and service innovation had a positive impact on intention to purchase, while 2) service innovation was a mediating variable that has a partial mediating effect between brand personality and social capital to increase intention to purchase. The results of this study can be used as a guideline for studying business models that need to offer products or services to LGBTQ+ groups and can be used in theory and application to allow businesses to reach new groups of consumers who have never been able to reach them before.